2009
DOI: 10.1017/s1368980009991364
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an educational intervention on complementary feeding practices and growth in rural China: a cluster randomised controlled trial

Abstract: Objective: Inappropriate complementary feeding is one of the major causes of malnutrition in young children in developing countries. We developed an educational intervention, delivered by local health-care providers, aimed at improving complementary feeding practices and child nutrition. Design: Eight townships in Laishui, a rural area in China, were randomly assigned to the educational intervention or control group. A total of 599 healthy infants were enrolled at age 2-4 months and followed up until 1 year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 21 publications
8
80
2
11
Order By: Relevance
“…Os resultados do presente estudo corroboram esse pressuposto, pelo menos em parte. Outros trabalhos têm demonstrado a influência dos profissionais de saúde na melhoria da alimentação infantil 27,28,29,30,31,32,33,34 . Destacamos a metanálise realizada por Sunguya et al 35 , que comprovou que a capacitação em nutrição dos profissionais de saúde melhorou a ingestão de energia, a frequência alimentar e a diversidade da dieta de crianças de 6 a 24 meses.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os resultados do presente estudo corroboram esse pressuposto, pelo menos em parte. Outros trabalhos têm demonstrado a influência dos profissionais de saúde na melhoria da alimentação infantil 27,28,29,30,31,32,33,34 . Destacamos a metanálise realizada por Sunguya et al 35 , que comprovou que a capacitação em nutrição dos profissionais de saúde melhorou a ingestão de energia, a frequência alimentar e a diversidade da dieta de crianças de 6 a 24 meses.…”
Section: Discussionunclassified
“…Alguns poucos trabalhos investigaram o efeito de intervenções no consumo dos alimentos saudá-veis (verduras, legumes e frutas), com resultados discrepantes 28,32 . Um deles, um ensaio clínico randomizado conduzido em oito comunidades na Índia 28 , testou a eficácia de uma intervenção educacional realizada por profissionais de saúde após capacitação para promover práticas adequadas de alimentação complementar.…”
Section: Pesquisa De Prevalência De Aleitamento Materno Nas Capitaunclassified
“…Esse resultado reflete as prioridades das práticas alimentares preconizadas na atualização realizada aos profissionais de saú-de com base na diretriz nacional para crianças menores de dois anos 24 , considerando a elevada prevalência de anemia entre crianças de 6 a 24 meses 31 e a importância de se fornecer ferro de alta biodisponibilidade quando da introdução da alimentação complementar 32 . Estudos de intervenção que incluíram indivíduos com faixa etária semelhante à das crianças desse estudo também demonstraram que as mães de baixa condição socioeconômica, quando orientadas, melhoram a oferta de fontes proteicas na alimentação complementar 20,21,33 . No período de 12 a 15 meses, o impacto ficou restrito ao consumo de frutas no grupo de US-ESF.…”
Section: Discussionunclassified
“…In addition, even when food resources are available in the home, caregivers might not make the best use of them due to lack of knowledge of the best foods for young children, cultural beliefs and practices, and inappropriate advice (14)(15)(16) . Studies on young children's feeding practices in other countries have demonstrated evidence that educational interventions have positive effects on knowledge of caregivers, complementary feeding practices and growth among children (17)(18)(19)(20)(21) .…”
mentioning
confidence: 99%